2015
DOI: 10.1167/15.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the rate of visual information processing

Abstract: Multiple methods exist for measuring how age influences the rate of visual information processing. The most advanced methods model the processing dynamics in a task in order to estimate processing rates independently of other factors that might be influenced by age, such as overall performance level and the time at which processing onsets. However, such modeling techniques have produced mixed evidence for age effects. Using a time-accuracy function (TAF) analysis, Kliegl, Mayr, and Krampe (1994) showed clear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 85 publications
(143 reference statements)
3
27
0
Order By: Relevance
“…It is important to highlight that processing speed is related to capacity for both visual and verbal active rehearsal. Processing speed has previously been shown to be particularly important in visuo-spatial tasks (Brown et al 2012, Bopp & Verhaeghen, 2007Guest et al 2015;Jenkins et al 2000), and an ability that is important in cognitive aging more generally (Salthouse, 1991(Salthouse, , 1996; see also Bucur et al, 2008;Deary et al, 2006;Deary, Johnson, & Starr, 2010). Indeed, Brown et al (2012) showed that the greatest predictor of older adults' performance of the most abstract version of the present visual working memory task was processing speed.…”
Section: Visuo-spatial and Verbal Working Memory Subsystemsmentioning
confidence: 77%
See 2 more Smart Citations
“…It is important to highlight that processing speed is related to capacity for both visual and verbal active rehearsal. Processing speed has previously been shown to be particularly important in visuo-spatial tasks (Brown et al 2012, Bopp & Verhaeghen, 2007Guest et al 2015;Jenkins et al 2000), and an ability that is important in cognitive aging more generally (Salthouse, 1991(Salthouse, , 1996; see also Bucur et al, 2008;Deary et al, 2006;Deary, Johnson, & Starr, 2010). Indeed, Brown et al (2012) showed that the greatest predictor of older adults' performance of the most abstract version of the present visual working memory task was processing speed.…”
Section: Visuo-spatial and Verbal Working Memory Subsystemsmentioning
confidence: 77%
“…Noack et al therefore concluded that age mainly affects the encoding stage of their task, and that both reduced storage capacity and less distinct neural activation can account for age-related limitations in visual working memory. Using time-accuracy function analysis (Kliegl, Mayr, & Krampe, 1994), Guest, Howard, Brown, and Gleeson (2015) observed age-related slowing of visual processing, specifically with multiple object arrays. This slowing was observed when the task involved processing and filtering out distractors at encoding, and also when required to encode more than one object into visual working memory for possible recall.…”
Section: Aging Effects On Visual Working Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a reduction in the benefit of information accrual over time when right parietal function is inhibited. Speed of information accrual has been shown to be sensitive to several factors including the presence or absence of distractors (Kent, Howard & Gilchrist, 2012) and set size (Guest et al, 2015). If visual information about the target stimulus is accrued more slowly, then this would lead to the pattern of performance we see here with little or no difference effects at the very shortest durations with an emerging difference at longer, though still brief (< quarter of a second), durations.…”
Section: Discussionmentioning
confidence: 74%
“…The speed of visual information accrual is known to exhibit individual differences (Guest et al, 2015). VGPs show more semantic priming than NVGPs when semantic primes are very brief (20 ms) but not when they are presented for longer (60 ms) (Pohl et al, 2014), suggesting that more visual information is processed by VGPs during these very brief intervals.…”
Section: Discussionmentioning
confidence: 99%